TINJAUAN TERHADAP TATA RUANG PERPUSTAKAAN SMA NEGERI PLUS TINGKAT PROPINSI DI KOTAMADYA JAKARTA BARAT - Septian Nurhakim (Shaut Al-Maktabah : Jurnal Perpustakaan, Arsip dan Dokumentasi, 2019)
This study discusses library layout, especially spatial planning in the school library. The sample taken was at the Library of Junior High School Plus Provincial Level in West Jakarta. The purpose of this study was to determine the condition of the Library of Junior High School Plus Provincial Level in West Jakarta and to find out whether this library was in accordance with the Guidelines for Organizing School Libraries published by the National Library in 2006. The method used in this study is descriptive method that is quantitative. The use of this method is supported by data collection by direct observation to the research site, which is then recorded on the research observation sheet. This study will assess several aspects of spatial planning from the school library. The results of this study represent the percentage of each school library, whether it is in accordance with the standard or not. For the Library of Public High School 112 Jakarta got an average score of 92.2% of the standard, while for the Library of Public High School 65 Jakarta got an average score of 76.6% of the standard, and for the Library of SMA 2 Jakarta got an average score of 86 % of standard. Thus, it can be concluded that the Library at the Provincial Level Plus High School in West Jakarta does not yet exist in accordance with the standards contained in the Guidelines for Organizing School Libraries published by the National Library of 2006. Therefore, researchers advise each school library to pay more attention. and developing the library especially in terms of spatial planning.